(untitled) (Al-Qamar, 2022)
Although the broad thrust of Qur’ān and Hadith favors religious liberty as Islam views all human beings the creation of God and blessed with intellect, wisdom, free will, and ability to discern between right and wrong! As HE Almighty has ordained in Qur’ān :The lights of clear perception have now come to you from your Lord. Then, he who chooses to see clearly, does so for his own good; and he who chooses to remain blind, does so to his own harm. I am not your keeper (Surah al-An‘ām: 6: 104). Thus a Muslim’s duty is to act in defense of what is right as much as his faith requires to oppose wrong. In this regard argue or altercation is in fact the name of that intensity which reveals the right and clearance of the statements in which someone defends himself from the opinions of his opponents with evident and proofs. Literally, the meaning of the word “Jadal” (جدل) is to argue or altercate severely and it is used for one who is stern in battle. The meaning of “Jadal al-Sarīh” (جدل الصريح) in Arabic terms is as they say (غلبته) which means he kept his conflict with the opposition until he was defeated by him. In the term of Sharīʻah it means to bring stronger arguments in comparison with the strong ones. It is appreciated in the case of finding and clarification of the right otherwise it is rejected. However, this article is divided into four major points of discussion. The study comprises, firstly, the definition and origin of the dialecticism, Its objectives secondly, its factors which lead to the proliferation of argument in the Islamic community thirdly and principles of Islamic dialecticism fourthly.